Pengaruh Likuiditas Saham Terhadap Excess Leverage pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia - Warzukni, Asyifa; Rasyid, Rosyeni (Financial Management Studies, 2023)
This study aims to analyze the effect of stock liquidity on excess leverage proxied by Excess Book Leverage (Booklev) and Excess Market Leverage (Marketlev) in manufacturing companies listed on the Indonesia Stock Exchange. This study uses three control variables, namely Return on Asset (ROA), Size, and Tangibility. The population in this study is all manufacturing companies listed on the Indonesia Stock Exchange in 2017-2021 totaling 232 companies. While the number of samples in this study amounted to 51 companies determined by the purposive sampling method and obtained a total of 255 data. The type of data used in this study is pre-existing data, obtained from the IDX Fact Book and the annual report of the sample companies. The analysis approach applied is to use multiple linear regression methods. From the results of the study, it can be concluded that there is a negative and significant relationship between stock liquidity with Excess Book Leverage (Booklev) and Excess Market Leverage (Marketlev) in manufacturing companies listed on the Indonesia Stock Exchange.